A jugoszláv utódállamok fragmentálódó városhálózata - Reményi, Péter (Közép-Európai Közlemények, 2011)
Several new states were born due to the breakup of former Yugoslavia, the running and length of state borders changed significantly. Furthermore, the way and the process of the break up of Yugoslavia impacted the transformations of the settlements and their network heavily. Today one can see the political geographical processes as the most important factors of the long-term development of the settlements of the former Yugoslavia.Beside the alteration of the settlement network, the shifts in the positions of the individual cities is a characteristic feature as well. It is possible to identify both winners and losers of the changes having taken place, experience of growth and also of decline which are all indicated mainly by transformations of and shifts in the functions and the number of people using these functions.